1998
DOI: 10.1097/00001648-199809000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Time-Series Analysis of Air Pollution and Cause Specific Mortality

Abstract: To investigate whether factors influencing ovarian function affect risk of uterine leiomyomata, we examined prospectively the association of new diagnoses confirmed by ultrasound or hysterectomy with body mass index, weight change, height, and cigarette smoking among 94,095 premenopausal women with intact uteri, who were ages 25-42 years at the start of follow-up in 1989. We assessed body mass index and cigarette smoking from responses on the study questionnaire completed just before diagnosis. During 322,775 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
3
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 35 publications
9
109
3
6
Order By: Relevance
“…Our findings are corroborated by studies that have investigated effects on other CVD outcomes, for example, hospital admissions and mortality. Internationally, ambient air pollutants have been associated with both hospital admissions for CVD (Ponka and Virtanen, 1996;Schwartz, 1999;Pope, 2000;Morris, 2001;Koken et al, 2003;Tsai et al, 2003) and mortality from CVD (Zmirou et al, 1998;Pope, 2000;Kwon et al, 2001;Hong et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are corroborated by studies that have investigated effects on other CVD outcomes, for example, hospital admissions and mortality. Internationally, ambient air pollutants have been associated with both hospital admissions for CVD (Ponka and Virtanen, 1996;Schwartz, 1999;Pope, 2000;Morris, 2001;Koken et al, 2003;Tsai et al, 2003) and mortality from CVD (Zmirou et al, 1998;Pope, 2000;Kwon et al, 2001;Hong et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Land transport and in particular road transport has a considerable negative influence on air quality. Evidence on health impacts of air pollution has been gathered through numerous studies conducted by scientists of various disciplines and published since the late 1980s (Pope, 1989(Pope, , 2000Pope et al, 1995Pope et al, , 2002Brunekreef et al, 1995;Brunekreef and Holgate, 2002;Brunekreef and Forsberg, 2005;Zmirou et al, 1998;Ję drychowski, 2000;Nyberg et al, 2000;Schwartz, 2000;Peters et al, 2000Peters et al, , 2001Katsouyanni et al, 2001;Hoek et al, 2002;Leikauf, 2002;Brook et al, 2004;Boldo et al, 2006;Naess et al, 2007). The results of such studies have been condensed and comprehensively evaluated in several WHO publications (WHO, 2000(WHO, , 2002(WHO, , 2005a and in relation to land transport impacts in WHO (2003); Krzyzanowski et al (2005) and WHO (2006).…”
Section: Impacts On Air Quality and Healthmentioning
confidence: 99%
“…A number of epidemiologic studies have shown a positive association between ambient levels of particulate matter ( PM) and various cardiorespiratory outcomes using mortality, hospital admissions, and emergency department ( ED ) admissions data (e.g., Thurston et al, 1994;Pope, 1996;Lipsett et al, 1997;Poloniecki et al, 1997;Schwartz, 1997;Schwartz et al, 1993Schwartz et al, , 1996Prescott et al, 1998;Zmirou et al, 1998;Burnett et al, 1999;Tolbert et al, 2000;see USEPA, 1996 for review ). Because PM is a heterogeneous mixture that varies in composition temporally and spatially, there is a need to identify agents within this mixture that may be responsible for the observed associations.…”
Section: Introductionmentioning
confidence: 99%